Peran Sense of humor dan Emotional intelligence terhadap Resolusi Konflik Dual-earner couples di Awal Pernikahan - Azizah, Wanda Rizki; Setiawan, Jenny Lukito (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
The divorce rate among dual-earner couples in the early years of marriage has increased in Indonesia, partly due to unresolved conflicts. This study aims to examine the influence of sense of humor and emotional intelligence on conflict resolution among dual-earner couples. A quantitative correlational method was used with 135 participants (52 husbands and 83 wives) in Jombang who had been married for a maximum of 10 years. The instruments used were the Multidimensional Sense of Humor Scale, The Assessing Emotions Scale, and the Conflict Resolution PREPARE/ENRICH Customized Version. Multiple regression analysis showed that both variables had a significant simultaneous effect on conflict resolution. The greatest contribution was found in sense of humor, which had a negative effect on conflict resolution, while emotional intelligence was significant only among male participants. These findings highlight the importance of appropriate humor use and emotional regulation skills in strengthening marital relationships.